The Fourth Energy Transition and Development of Energy Sector in Kazakhstan - BAKTYMBET, Assem S.; BAKTYMBET, Saule S.; YELSHIBAYEV, Rakymzhan K.; UKUBASSOVA, Galiya S.; BAKTYMBET, Aisara S. (Journal of Advanced Research in Law and Economics; Vol 11 No 3 (2020): JARLE Volume XI Issue 3(49) Summer 2020DO - 10.14505/jarle.v11.3(49).05, 2020)
The relevance of the subject matter is conditioned upon the fact that currently the main direction of global energy development is already clearly visible: under the influence of changes in energy policy and the development of new technologies, the world is entering the stage of the fourth energy transition to the widespread use of renewable energy sources and displacement of fossil fuels. The development of Kazakhstan's economy requires the transition of energy towards clean and safe renewable sources, which will let the country build a new strong economy and break out of the long-running socio-economic decline, help the international community solve the problem of climate change and improve the safety and welfare of its citizens. The purpose of the study: The purpose of the paper is to develop recommendations for the development of Kazakhstan's energy industry at a new stage in the fundamental transformation of the global energy system. Leading approach to researching the problem. The leading methods of researching the problems of the paper include the analysis of theoretical sources, analysis of statistics, and comparison. Analysis of statistical indicators plays a crucial role in the study, since data on the development of Kazakhstan's energy industry can be directly obtained from statistical databases. The results of the study. The paper discusses the essence of the fourth energy transition, its main aspects, explores renewable energy sources, identifies the features and problems of Kazakhstan's energy industry, and develops ways to solve them. Prospects for further research. To implement the modern provisions of the fourth energy transition in Kazakhstan, it is necessary to use a systematic approach. The basic elements of such a transition are the introduction of renewable energy and energy efficiency (the intensification of reducing the energy intensity of goods and services). The materials of the paper are of practical value for the development of Kazakhstan’s energy during the period of fundamental structural transformations of the world energy sector.